THE INFLUENCE OF EMPOWERING LEADERSHIP STYLE ON EMPLOYEE PERFORMANCE WITH TRAINING AS A MODERATING VARIABLE - Eri Mardiani; Teguh Setiawan Wibowo; Arief Setiawan; Rini Fatmawati; Magdalena Linda Leonita Sibarani (JURNAL ILMIAH EDUNOMIKA, 2024)
Abstract This research adds the Training variable as a moderating variable which researchers believe can strengthen the influence of the Empowering Leadership Style variable on Employee Performance and the Training variable is believed to strengthen the influence of the Empowering Leadership Style variable on Employee Performance. This research is quantitative research with an explanatory approach that uses previous research as old records regarding Empowering Leadership Style, Employee Performance, and Training to find newness in this research. The data in this research is included in the primary data group because it was obtained directly from the data source through distributing online questionnaires to 300 motor vehicle sales spread throughout Indonesia. The data is analyzed using the smart PLS 4.0 analysis tool. Keywords: Empowering Leadership Style, Employee Performance ,Training